A comprehensive diagnostic scheme of morphological combined molecular methylation under bronchoscopy - Zhang, Jinze; Huang, Haoran; Yu, Fan; Bian, Yuanyuan; Wang, Rui; Liu, Hui; Kang, Saisai; She, Bin; Shi, Zhihua (Frontiers in Oncology, 2023)
Methylated SHOX2 and RASSF1A genes are potential biomarkers for lung cancer diagnosis. Therefore, we explored the role of methylation detection combined with morphological bronchoscopic evaluation for lung cancer diagnosis. Bronchoscopy, methylation outcome, and pathological data were collected from 585 patients with lung cancer and 101 controls. The methylation status of the SHOX2 and RASSF1A genes were detected using real-time polymerase chain reaction quantification. Further, the sensitivity and area under the receiver operating characteristic curve of the three methods were analyzed. Among 686 patients, 57.1% had new organisms detected through bronchoscopy and 93.1% of these patients were diagnosed with malignant tumors. Besides, 42.9% of patients had no visible changes under bronchoscopy but there were still 74.8% of them diagnosed with malignant tumors. Bronchoscopy revealed that lung adenocarcinoma, lung squamous cell carcinoma, and small cell lung cancer mainly occurred in the upper and middle lobes. The sensitivity and specificity of methylation detection were 72.8% and 87.1% (vs. cytology 10.4% & 100%), respectively. Therefore, methylated SHOX2 and RASSF1A genes may be a promising tumor marker in lung cancer diagnosis. Methylation detection can be an excellent supplementary tool for cytological diagnosis and, combined with bronchoscopy, could form a more effective diagnostic process.